Alterations of the hematologic cells in synthetic cannabinoid users. Issue 6 (7th February 2017) - Guzel, Derya; Yazici, Ahmet Bulent; Yazici, Esra; Erol, Atila
Abstract : Background: Functions, morphology, distributions, and index of the circulating cells are the most useful parameters that indicate various inflammatory and toxic conditions. The aim of this study was to investigate the clinical significance of these parameters in patients diagnosed with (synthetic) cannabis use disorder. Methods: This study included a total of 40 patients in the study group (SG) with synthetic cannabis use; and 40 healthy individuals as the control group (CG). Participants, who had hematological disorders and other chronic diseases, were excluded from the study. All hematological parameters of SG were compared with CG. Neutrophil/lymphocyte ratio (NLR) and platelet/lymphocyte ratio (PLR) values were calculated and compared between groups. Results: There were statistically significant differences between the groups in terms of WBC, MCH, RDW, MCV, MPV, and NEU, LYM%, MONO% parameters ( P <.05). MPW and LYM% were significantly lower in SG compared to CG. WBC, MCH, RDW, MCV, MPV, MONO, and NEU parameters were significantly higher in SG compared to CG ( P <.05). UIBC and TIBC levels were significantly higher in SG compared to CG ( P <.001). Although there was statistically significant difference between groups in terms of NLR, there was no significant difference for PLR values. Conclusion: Our data suggested that chronic use of cannabinoids can lead to deterioration of hematopoietic cells. Chronic use of cannabinoids was consistent with subthreshold/subclinical megaloblastic anemia with iron deficiency. Inflammatory cells, especially neutrophil and monocyte counts were higher in SG compared to CG. Thus, recovery of subclinical hematological parameters should be considered in cannabis use disorder patients.